2014
DOI: 10.1007/s00213-014-3636-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impact of cytotoxic agents in mice

Abstract: Our data show that, in mice, a single treatment with a cytotoxic agent causes cognitive impairment. Not all cytotoxic agents affected the same cognitive domains, which might be explained by differences in working mechanisms of the various agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 58 publications
6
75
1
Order By: Relevance
“…Some rodent studies have reported that chemotherapy significantly decreased hippocampal neurogenesis [11,12]. In previous reports, it was described that 5-fluorouracil and methotrexate inhibited both cell proliferation in the hippocampal dentate gyrus and hippocampal-dependent working memory in rats [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some rodent studies have reported that chemotherapy significantly decreased hippocampal neurogenesis [11,12]. In previous reports, it was described that 5-fluorouracil and methotrexate inhibited both cell proliferation in the hippocampal dentate gyrus and hippocampal-dependent working memory in rats [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence in rodents supports the contention that chemotherapy-induced cognitive deficits can be present without appreciable, or with only modest, changes to neurobiological parameters. In tumor-free mice, the one-time administration of cytotoxic chemotherapeutic agents at doses that caused deficits in various cognitive measures (Seigers et al, 2015) had no effect, in the same model, on neurogenesis and microglial activation in the hippocampus at 3 or 16 weeks after treatment, and had modest effects on microgial activation in the prefrontal cortex at 3, but not 16, weeks post-treatment (Seigers et al, 2016). This study echoes our own in the doses used, in the timing of agent administration and endpoint evaluation, and in the results generated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 5 daily administrations of the chemotherapeutic agent cytosine arabinoside results in deficits in long term (30 day), but not short term (1 day), recall in the Morris water maze and is associated with reductions in length, branching and spine density of apical dendrites in the anterior cingulate cortex [166], suggesting that the observed cognitive deficit is a consequence of structural changes induced by drug exposure. Lastly, deficits in spatial memory are observed in the Barnes maze 30 days following exposure to doxorubicin or topotecan [85]. These data indicate that exposure to several chemotherapeutic agents can lead to persistent impairments in acquisition and performance of spatial memory tasks.…”
Section: Spatial Memorymentioning
confidence: 94%
“…Although deficits in attention are commonly observed in patients suffering from 'chemo-brain,' to date, few animal studies have focused on attentional deficits following exposure to chemotherapeutic agents. Recently, Seigers et al [85] used a simple choice reaction time task following exposure to several different chemotherapeutic agents and determined that cyclophosphamide, docetaxel and topotecan each produced deficits in attention and inhibitory control 40 days following a single exposure. Additionally, a recent study with temozolomide examined hippocampal theta activity, which is associated with attention to a stimulus [86][87][88][89][90][91], and found that this compound reduced theta activity during classical conditioning and that this reduction was associated with impaired learning [92].…”
Section: Attention and Working Memorymentioning
confidence: 99%
See 1 more Smart Citation